Synthesis of Analogs of a Potential Drug for Treatment of Epilepsy - Fluet-Chouinard, Adrien (Université d'Ottawa / University of Ottawa, 2019)
Prior work in the Durst group had generated more than forty analogs of the potent anticonvulsant isoxylitone isolated isolated from a medicinal plant Delphinium denudatum Wall. The nitrile designated as TD532 was the most potent compound generated by A. Saikaley. The starting material for the synthesis of TD532 is isophorone. The observation that TD532 showed considerable potential as an anticonvulsant suggested that other cyclohexenones might have have similar activity. During this project close to fifty derivatives of cyclohex-2-enone, focusing mainly on 3-arylcylohex-2-enones, were prepared. The synthesis of these compounds is described and structure activity relationships are discussed. Based on all the available structure activity data, we have designated the indicated portion of structure A as the pharmacophore for anticonvulsant and anti-epileptic activity. The ester designated as TD561 (compound 40) showed excellent potential in both in vitro and in vivo assays. It has been shown to be a pro-drug of the corresponding acid TD562 (compound 48). These two compounds and the sodium salt of TD562 are currently undergoing final pre-clinical studies at the Center for Drug Research and Development in Vancouver. Five analogs, including TD561 are also under investigation by the Epilepsy and Seizure Division of the US National Institutes of Health.
Keywords: Synthesis of Analogs; Potential Drug; Treatment of Epilepsy; Anti-epileptic drug; Structure-activity relationship